PRINCIPAL'S STRATEGY IN IMPROVING TEACHER PERFORMANCE AT SMK NEGERI 1 BANYUDONO BOYOLALI - Kewa, Sukmawati Putri Jamalia Ina; Jinan, Mutohharun (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to describe the leadership of school principals in improving teacher performance at SMK Negeri 1 Banyudono Boyolali. The methodology of this research uses a descriptive qualitative approach, namely information in the form of letters rather than numbers. The key to this research is the principal and the teacher. This is because the principal and teachers are directly involved in the learning process at SMK Negeri 1 Banyudono Boyolali. The data collection techniques are observation, interviews and document studies. The leadership of the principal is expected to have the ability to move, influence, motivate, direct, and nurture teachers, so that a high work ethic, creativity and productivity are born in achieving goals. Teacher performance is the result of teachers' work that is reflected in how to plan, implement, and assess the teaching and learning process. The results of the study show that the leadership of school principals in improving teacher performance is good, namely the commitment to enforce the discipline of teachers' working time in schools and provide motivation for teachers and empower teachers by paying attention to their achievements in improving their work ethic. Teachers' performance improved with the enforcement of discipline and teachers' work motivation at school, both including their presence at school and class, discipline in presenting subject matter and punctuality when leaving the classroom after completing the subject matter. Motivation and Empowerment of teachers by paying attention to their achievements in improving their work ethic and providing awards, congratulations, and appreciation either in the form of charters or incentives for outstanding teachers. Thus, it was concluded that the leadership of the principal in improving the performance of teachers at SMK N 1 Banyudono Boyolali greatly contributes to the progress of learning quality so that it can encourage the quality of education and success in the world of education, especially at SMK N 1 Banyudono Boyolali.